Novel four-in-one intumescent flame retardants for polypropylene: Synthesis, characterization and properties - Yu Zhang; Xiaowei Zhao; Xiaohong Li; Zhijun Zhang; Zhiwei Li (Advanced Industrial and Engineering Polymer Research, 2024)
To address the shortcomings of traditional intumescent flame retardants (IFRs), a novel four-in-one IFR (M [APP/NiCo2O4]) was constructed for the first time. It integrates acid source, gas source, carbon source (crosslinking β-CD), and synergistic agent (NiCo2O4 nanoparticles) into a single entity by a co-encapsulation technology. Under the loading of 20 wt%, its flame retardant performance was significantly better than that of simple mixed flame retardants, and it could increase the limiting oxygen index of polypropylene (PP) from 18 to 30.2 and pass the UL-94 V-0 rating. At the same time, it could reduce the peak of heat release rate, total heat release, and peak of CO production of PP by 77%, 22%, and 80%, respectively, showing excellent flame retardant performance. The excellent flame retardant performance is mainly because the synergist NiCo2O4 nanoparticles in the four-in-one flame retardant can easily combine and efficiently interact with the acid source, carbon source, and gas source in the intumescent flame retardant to form a more stable protective char residue. In addition, the crosslinking β-CD shell enhances both the water resistance and initial thermal decomposition temperature of PP containing the four-in-one IFR compared to PP with simple mixed control samples. After 72 h of water resistance test, it can still maintain the UL-94 V-0 rating. The presence of the crosslinking β-CD shell also improves the compatibility of the four-in-one flame retardant in PP, and its adverse effects on the mechanical properties of PP are also significantly smaller than those of the mixed control sample.